Gaya Kepemimpinan Kepala Sekolah dan Motivasi Dalam Meningkatkan Kinerja Guru - Desy Irana Dewi Lubis (Jurnal Bisnis dan Manajemen (JURBISMAN), 2023)
The headmaster in a school, has an important role in carrying out activities in the world of education. The headmaster also has distinctive characteristics in leading. Giving motivation and other things continues to be done so that teachers and workers under their auspices can continue to develop. This research was conducted to see the effect of the headmaster's leadership style and motivation on teacher performance at SMK PAB 3 Medan Estate. With a sample of 30 people consisting of teachers and workers, with a sampling technique that is saturated sampling. The research method used is descriptive quantitative and the data analysis method uses multiple coefficient tests, using SPSS version 22. The results showed an R2 value of 87.3%, meaning that the leadership style and motivation variables were able to explain the variations that occurred in the performance variable, the partial test results showed a variable value of leadership style of 4.110 and a motivation variable of 2.812 and a simultaneous test result value of 92.716. This means that simultaneously and partially the results of this study have a positive and significant effect.